2018
DOI: 10.1111/dar.12826
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol industry involvement in science: A systematic review of the perspectives of the alcohol research community

Abstract: IssuesAlcohol companies have recently invested large sums of money in answering research questions to which they have clear vested interests in the outcomes. There have been extensive concerns about corporate influence on public health sciences, following the experience with the tobacco industry.ApproachThis systematic review aims to investigate the perspectives of researchers on the activities of alcohol industry actors in relation to science, in order to guide future research. All data published in peer‐revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 167 publications
0
64
0
Order By: Relevance
“…Despite the termination of the trial, however, the data analysed suggests that alcohol industry actors benefited from their donations in other ways, including gaining insight into alcohol research and policy both at the U.S. and global level. Concerns have been raised within the scientific community about ICAP and IARD's role in science 21 and policy, 12 and this particular case demonstrates the need for further study of IARD's ongoing activities, especially relationship-building with researchers and officials. We encourage the NIAAA to recognise the need to strengthen the alcohol policy evidence-base by funding research on industry's commercial, political, and scientific activities.…”
Section: Scientific Health and Policy Implicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite the termination of the trial, however, the data analysed suggests that alcohol industry actors benefited from their donations in other ways, including gaining insight into alcohol research and policy both at the U.S. and global level. Concerns have been raised within the scientific community about ICAP and IARD's role in science 21 and policy, 12 and this particular case demonstrates the need for further study of IARD's ongoing activities, especially relationship-building with researchers and officials. We encourage the NIAAA to recognise the need to strengthen the alcohol policy evidence-base by funding research on industry's commercial, political, and scientific activities.…”
Section: Scientific Health and Policy Implicationsmentioning
confidence: 95%
“…14 Unlike the tobacco industry, there are few accessible internal alcohol company documents that permit direct insights into how strategies are developed and executed to bias science or influence policy. 12,21 Further study of this episode could include broadening the dataset to include related information in the public domain, and identifying ICAP/IARD interactions with the NIAAA, other publicly funded bodies, and relationship building with researchers. Alcohol companies were key actors in the MACH trial, and we know little about their involvement in science more generally.…”
Section: Scientific Health and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These documents have revealed the many ways through which that industry tried to avoid, weaken and delay the development of tobacco control policies [49,50,54,55]. There is growing evidence that other companies in the food [29,30,56,57], alcohol [58][59][60], gambling [61][62][63], automobile, and chemicals industries [19,31,64], for example, use similar political practices. In public health, these political practices are usually classified into two categories [49]:…”
Section: Corporations and Practices Harmful To Healthmentioning
confidence: 99%
“…89 A recent meta-analysis assessing the role of the alcohol industry in science concluded that there are serious concerns in at least 3 areas: on evidence-informed policy making, on the processes of undertaking research and on the content of the scientific evidence base itself. 90 One of the most striking examples is a $100 million, 9nation clinical trial, which was mostly funded by major producers to evaluate the health benefits of a single dose of alcohol given daily to individuals at risk of coronary heart disease. This study was terminated early by government agencies in the US.…”
Section: Control Over Alcohol Advertising and Promotionmentioning
confidence: 99%